Setembro de 1889, tramas de uma primavera recifense: os casos Chrispim e Ricardo Guimarães. - Salvari, Fábio Maurício (2019)
After 1870, the government of D. Pedro II lost much credibility before the oligarchy and the military. To understand the plots and their consequences were used as sources newspapers, magazines, bulletins of occurrence. The aim was to understand the vulnerability of political institutions in the late nineteenth century that served local political interests. Republicans, Liberals, and Conservatives in the midst of a political power-play that carried forward in the struggles that took place in Brazilian political centers.The Second Empire's political disputes between Liberals, Conservatives and Republicans are analyzed from three plots that had taken place between August and September 1889. The Antônio Chrispim case and the Ricardo Guimarães case unfolded in Recife, in the Pernambuco province. The two cases had repercussions in the main newspapers of the capital. The ascension of the ministerial cabinet Visconde de Ouro Preto of the Liberal Party was on June 6, 1889.